This or not that: select and reject control of relational responding in rats using a blank comparison procedure with odor stimuli - Bobbie Faith Wolff; Mark Galizio; Katherine Bruce (Animal Cognition)
Abstract The blank comparison (BLC) task was developed to assess stimulus relations in discrimination learning; that is, are subjects learning to “select” the correct stimulus (S+) or “reject” the incorrect stimulus (S-) or both? This task has been used to study exclusion learning, mostly in humans and monkeys, and the present study extends the procedure to rats. The BLC task uses an ambiguous stimulus (BLC+/-) that replaces S+ (in the presence of S-) and replaces S- (in the presence of S+). In the current experiment, four rats were trained to remove session-novel scented lids from sand-filled cups in a two-choice, simultaneous presentation procedure called the Odor Span Task (OST) before being trained on the BLC procedure using odors as the discriminative stimuli. The BLC training procedure utilized simple discrimination training (S+ and S-) and added select (S+ and BLC-) and reject (BLC+ and S-) trial types. All rats demonstrated accurate performance in sessions with both select and reject type trials. Next, BLC probe trials were interspersed in standard OST sessions to assess the form of stimulus control in the OST. Rats performed accurately on select type probe trials (similar to baseline OST performance) and also showed above chance accuracy on reject type trials. Thus, we demonstrated that rats could acquire an odor-based version of the BLC task and that both select and exclusion-based (reject) relations were active in the OST. The finding of exclusion in rats under the rigorous BLC task conditions confirms that exclusion-based responding is not limited to humans and non-human primates.